Updates on tetanus toxin: a fundamental approach - Ahaduzzaman, Md. (Journal of Advanced Veterinary and Animal Research, 2014)
NOTE: on 05/01/2015 the name of the author was changed from Asaduzzaman TO Ahaduzzaman on the website. The PDF was correct. Clostridium tetani is an anaerobic bacterium that produces second most poisonous protein toxins than any other bacteria. Tetanus in animals is sporadic in nature but difficult to combat even by using antibiotics and antiserum. It is crucial to understand the fundamental mechanisms and signals that control toxin production for advance research and medicinal uses. This review was intended for better understanding the basic patho-physiology of tetanus and neurotoxins (TeNT) among the audience of related field. http://dx.doi.org/10.5455/javar.2015.b54